Past, current and future of biomass energy research: A bibliometric analysis. (December 2015) - Mao, Guozhu; Zou, Hongyang; Chen, Guanyi; Du, Huibin; Zuo, Jian
Abstract: This paper characterizes the body of knowledge on biomass energy from 1998 to 2013 by employing bibliometric techniques based on the Science Citation Index (SCI) databases of the Web of Science. Results showed that journal articles were the most frequently used document type representing 84.1% of the records. 33, 072 articles were analyzed on various aspects of the publication characteristics such as authorship, countries, institutions, high-cited papers, and keywords. The pace of publishing in this field increased rapidly over last 16 years, with the US accounting for the highest h -index (137) and the most publications (8228), followed by China and India. The US also plays a central role in the collaboration network among the most productive countries. The Chinese Academy of Science was the organization with the most records (639). Similarly, the University of Illinois is central to the collaboration network. The hot spots of biomass energy related researches were transiting from physical conversion (6511 articles) to thermal chemical conversion (10, 989) and biochemical (10, 877).The bioenergy application (18, 607) has become a main focus of current researches related to biomass energy. This topic mainly addresses biodiesel, biogas, biohydrogen, biofuel cell and so on. By identifying global hotspots in biomass energy research, this study is beneficial for researchers, e.g. the selection of future research topics. Similarly, policy makers will learn from the findings of this analysis with a good understanding of the status quo of biomass energy development.